2016
DOI: 10.5539/jas.v8n8p88
|View full text |Cite
|
Sign up to set email alerts
|

Study on Germination of Seven Barley Cultivars (Hordeum vulgare L.) under Salt Stress

Abstract: The present work aims to study the germination behavior of seven Tunisian varieties of barley (Kounouz, Faiz, Roho, Manel, Lemsi, Rihane and Tej) during germination without or with NaCl. These varieties have been chosen in order to have the greatest possible diversity on the agro-physiologic level and to select tolerant plants to salinity. Barley grains are germinated (in Petri dishes lined with a double layer of filter paper soaked) in a solution of NaCl 0, 50, 100, 150, 200 mM for 7days. Two germination crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The significant variations among the genotypes and genotypes × salinity interaction under four salinity levels indicate that there was a high genetic variation among the screened genotypes. Previous studies have also reported highly significant differences among genotypes and genotypes × salinity interaction for different traits such as germination, root, and shoot length (Abdi et al, 2016;Angessa et al, 2017;El Goumi et al, 2014;Tavili & Biniaz, 2009). Generally, mean root length decreased as the level of NaCl increased for all genotypes (Table 3).…”
Section: Salt Tolerance At Germination Stagementioning
confidence: 74%
See 3 more Smart Citations
“…The significant variations among the genotypes and genotypes × salinity interaction under four salinity levels indicate that there was a high genetic variation among the screened genotypes. Previous studies have also reported highly significant differences among genotypes and genotypes × salinity interaction for different traits such as germination, root, and shoot length (Abdi et al, 2016;Angessa et al, 2017;El Goumi et al, 2014;Tavili & Biniaz, 2009). Generally, mean root length decreased as the level of NaCl increased for all genotypes (Table 3).…”
Section: Salt Tolerance At Germination Stagementioning
confidence: 74%
“…Previous studies have also reported that there were significant variations in salt tolerance among barley genotypes at the germination stage (Kook et al, 2009;Tajbakhsh et al, 2006). Seed germination under salinity is reduced due to osmotic stress, and high levels of NaCl reduced the bioavailability of water caused by Na + , resulting in what is effectively an osmotically induced water deficiency (Abdi et al, 2016;Mano et al, 1996;Parida & Das 2005). Additionally, Na + displayed toxic effects on the germinating embryos (Mazher et al, 2007).…”
Section: Salt Tolerance At Germination Stagementioning
confidence: 97%
See 2 more Smart Citations
“…Corrected germination percentage (CG%) was used to identify physiological effects of salinity on seed germination (Abdi et al., 2016). It was calculated by using the formula of Smith and Dobrenz (1987): CG%=Nx/Nnormalo×100where N x is the germination percentage in x mM salinity treatment, and N o is the germination percentage in the control treatment.…”
Section: Methodsmentioning
confidence: 99%